Antibacterial and antioxidant effects of Zanthoxylum armatum DC extracts - Irshad, Aqsa; Ullah, Irfan; Khan, Muhammad Fiaz (Bangladesh Journal of Botany, 2021)
Antibacterial and antioxidant activities of three different extracts (acetone, methanol, and n-hexane) of Zanthoxylum armatum fruits and leaves were investigated. The maximum inhibition zone was shown by methanolic leaf extract against K. pneumonia (20.51 ± 0.93). The minimum inhibition zone (12.01 ± 0.93) was exhibited by methanolic fruit extract against S. typhi. The highest antioxidant activity was recorded at 1000 ppm. Methanolic leaf extract was the most antioxidant (89.8%) among all the extracts, followed by methanolic fruit extract (88.6%). The methanolic and acetonic extracts showed good antibacterial activity as compared to n-hexane extracts and n-hexane was less antioxidant.